Przesłanki realizacji nowej polityki spójności Unii Europejskiej w latach 2007-2013 - Klamut, Mirosława (New Cohesion Policy of the European Union in the Years 2007-2013, 2006)
There are big economic and social differences between different regions in the European Union countries. Also, spatial development is not uniform in different regions. Underdevelopment, stagnation and even backward regions, which require structural conversion, may receive assistance from structural funds. The author claims that more consistent integration between science, education, innovations and economic development of regions, is an important condition of Poland's integration with the European Union. This situation demands modifying the principles of regional policy, structure of goals of state's regional policy, and circumstances realization cohesion policy for years 2007-2013 presented in the second cohesion report.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 26-43